NOVEL POLYDIOXANONE - PLURONIC 127 OXYTOCIN IMPREGNATED MESH, PRELIMINARY STUDY OF OXYTOCIN RELEASE IN VITRO - MIRON (LUNGU), Andreea Elena; MOLDOVAN, Marioara; PRODAN, Doina; VLASSA, Mihaela; MOLDOVAN, Mădălina; ROMAN, Rareș Călin; BADEA, Mîndra Eugenia (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Polymers represent a novel alternative in bone regeneration. Polydioxanone combined with Pluronic was used as a carrier for Oxytocin in form of an interfacial deposition obtained scaffold. The low rate of resorption of the scaffold follow the bone regeneration sequence assuring a constant and continuous release of Oxytocin. The Oxytocin release was monitored by RP-HPLC method. The separation was performed on a Phenomenex Luna 5µm C18 100A, 250x4.6mm, using isocratic elution with acetonitrile: phosphate buffer pH 7 (30:70 v/v) mobile phase. Flow rate 1 ml / min, column temperature 30°C, DAD, l= 220nm. The surface morphology of polydioxanone - pluronic 127 - Oxytocin impregnated mesh was characterized by SEM. The preliminary results show that the Polydioxanone combined with Pluronic is a promising polymer for bone regeneration engineering.